1988
DOI: 10.1002/cne.902700206
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of peptides and other neurochemicals in the rat laterodorsal tegmental nucleus and adjacent area

Abstract: The laterodorsal tegmental nucleus (ntdl) contains a cluster of cells located just medial to the locus coeruleus in the pontine brainstem. The ntdl has been shown to project both rostrally to the forebrain and diencephalon and caudally to the spinal cord. In an effort to characterize this region neurochemically, the present study was conducted to identify a variety of neurochemicals localized within perikarya and fibers of the ntdl and surrounding nuclei. Rats were perfused with formalin, and brain sections we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(62 citation statements)
references
References 73 publications
4
57
1
Order By: Relevance
“…The present study was able to confirm all of these localizations with in situ hybridization histochemistry except the pedunculopontine tegmental nucleus, the accessory trigeminal nucleus, and the ventral nucleus of the trapezoid body. Several of these localizations have also been described in immunocytochemical (McGinty, 1985;Sutin and Jacobowitz, 1988;Moga et al, 1990;Van Bockstaele et al, 1995) and/or in situ hybridization histochemical (Young et al, 1986;Alvarez-Bolado et al, 1990) studies of restricted regions of the rat brain.…”
Section: Distribution Of the Expression Of The Preprodynorphin Genementioning
confidence: 90%
“…The present study was able to confirm all of these localizations with in situ hybridization histochemistry except the pedunculopontine tegmental nucleus, the accessory trigeminal nucleus, and the ventral nucleus of the trapezoid body. Several of these localizations have also been described in immunocytochemical (McGinty, 1985;Sutin and Jacobowitz, 1988;Moga et al, 1990;Van Bockstaele et al, 1995) and/or in situ hybridization histochemical (Young et al, 1986;Alvarez-Bolado et al, 1990) studies of restricted regions of the rat brain.…”
Section: Distribution Of the Expression Of The Preprodynorphin Genementioning
confidence: 90%
“…Peoples et al (2002) examined the ultrastructural associations of endomorphin-1 with the NA neurons of the LC and the peptidergic neurons of Barrington's nucleus in the brainstem dorsal pontine tegmentum. Both structures, targeted by endogenous opioids (Sutin and Jacobowitz, 1988;Van Bockstaele et al, 1996c) and enriched with -opioid receptors (Atweh and Kuhar, 1977;Van Bockstaele et al, 1996a,b), might be involved in the reduction of the excitability of the LC neurons caused by endomorphins (Peoples et al, 2002). It was demonstrated that endomorphin-1-immunoreactive axon terminals form synaptic specializations with tyrosine hydroxylase-and CRF-containing dendrites in peri-LC and Barrington's nucleus, respectively, in the dorsal pontine tegmentum of the rat brain.…”
Section: Modulation Of Noradrenaline Transmissionmentioning
confidence: 99%
“…Van den Bergh et al (1988) described the distribution of TRH, enkephalin, somatostatin, substance P, neurotensin, and peptide isoleucine histidine (PHI) cell bodies. Sutin and Jacobowitz (1988) analyzed neuropeptides in the most caudal part of the vPAG reporting on neurotensin, galanin, VIP, CCK, substance P, calcitonin gene-related peptide (CGRP), somatostatin, and atrial natriuretic factor. Smith et al (1994) compared the distribution of the transcripts for enkephalin, substance P, somatostatin, galanin, VIP, NPY, and CGRP at three different levels of the PAG.…”
mentioning
confidence: 99%